How did I catch your attention: An English novella and its writing process - Ingibjörg Rósa Björnsdóttir 1976- (2009)
This MA essay is the first Creative Writing final assignment to be completed in the English Department at the University of Iceland. It is the result of a Creative Writing course taught by Anna Heiða Pálsdóttir at the Department in the spring of 2007. The assignment consists of a novella, Flames of Guilt, and a report. The novella is around 20 000 words (65%), and the report is around 10 000 words (35%). The novella is a historical drama, revolving around an English family in Leicestershire, England, during World War I. Preparations and the process of writing the novella demanded quite a lot of background knowledge on England, its history and culture, its people and their way of thinking, as well as the English language. Therefore, I could put to use the knowledge and skills that I had acquired during my BA and MA studies at the English Department. However, when preparing the writing, I had to take a closer look at England from 1914-1918 and in order to do so, took a trip to England where I, for instance, spent two days visiting The Imperial War Museum in London. The report explains how Flames of Guilt came about, from the time it was a vague idea over a decade ago, until the moment I wrote the last sentence. It describes how I employed guidelines from textbooks on writing, the reasons for structuring the plot they way I did and my choice and of the characters and the descriptions of their traits. With this final assignment I not only hope to show my skills as a fiction writer but also my skills in writing creatively in another language than my own, English. With the report I hope to give some insight into the mind of a writer and how I have applied rules or guidelines on creative writing, e.g. about structure, conflict, climax and characterization.